Pembuatan Biodiesel Minyak Goreng Bekas dengan Memanfaatkan Limbah Cangkang Telur Bebek sebagai Katalis CaO - Inke Yolanda Wiyata (Jurnal Pengabdian Vokasi, 2021)
Application Study in Biodiesel Manufacturing Used Cooking Oil With Utilizing Duck Egg Shell Waste as CaO Catalyst to produce biodiesel from vegetable oil waste is motivated by the fact that the existing energy reserves are decreasing from time to time. Biodiesel is an alternative fuel, make from vagatable oil, animal fat, waste oil, and others. Through the process of esterification and transesterification by changing the catalyst concentration 2% and 4% CaO, working temperature 50⁰C and 60⁰C. The operating time is 110 minutes. The purpose of this research is to determine the best treatment method for the transesterification reaction, and to use a factorial analysismethod of 2 level 3 variable design to determine the main effect that has the greatest impact. In this study, the best transesterification condition was the eighth variable, the addition of 4% CaO (w/w), esterification time of 130 minuted and operating temperature of 60⁰C. The biodiesel characteristics obtained were viscosity value 3.8246 cSt, density 864,8 kg/m3, %yield was 81,4% and the cetane number was 38,0. The main effect that the most influential is % catalyst.